1973
DOI: 10.3758/bf03326918
|View full text |Cite
|
Sign up to set email alerts
|

The temperature of ingested water: Preference for cold water as an associative response

Abstract: l 'hni,) log/('(}II'.lTlh()I')gl' 1'1;3, lui. I .. \(), 3. _'57·~M) The tenlperaturc of ingested water: Preference for cold water as an associative response* EDWARD DEAUX and ROBERT ENGSTROM Antioch Collef(e. Yellow Springs, Ohio 4538;' Rah \\Trl' found to prd'l'r 12 OVl'r 36''C water when their choice was restricted to those temperatures, but no clear prefl'rl' nl'c was shown bl·twecn water of 12° and 24°C or 24° and 36°C. The hypothesis that preference for cooler \\;Iter is based on the animals' hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Fourth, cold increases cluster size, a measure of palatability in both water-restriction states (Davis 1989, Figure 2E,F), and lastly, cold increased licking to water in brief-access tests (Figure 5). There are a handful of previous studies in agreement including several preference tests (Deaux and Engstrom 1973;Ramsauer et al 1974;Smith et al 2010) and a study demonstrating that rats will bar press more for cold than warm water (Ramsauer et al 1974).…”
Section: Water-restriction Strengthens Cold Preferencementioning
confidence: 96%
See 1 more Smart Citation
“…Fourth, cold increases cluster size, a measure of palatability in both water-restriction states (Davis 1989, Figure 2E,F), and lastly, cold increased licking to water in brief-access tests (Figure 5). There are a handful of previous studies in agreement including several preference tests (Deaux and Engstrom 1973;Ramsauer et al 1974;Smith et al 2010) and a study demonstrating that rats will bar press more for cold than warm water (Ramsauer et al 1974).…”
Section: Water-restriction Strengthens Cold Preferencementioning
confidence: 96%
“…In 1-bottle short-term tests, rats drank more water when it was 30-35 °C and less when cool (12 °C) or warm (48 °C, Kapatos and Gold 1972). Interestingly, water-restricted rats preferred cool over warm water in short term 2-bottle tests (12 > 36 °C: Deaux and Engstrom 1973, 12 > 40 °C: Ramsauer et al 1974, 10 > 40 °C and 25 > 40 °C: Smith et al 2010) and bar pressed more for cold than warm water (12 > 40 °C: Ramsauer et al 1974) suggesting that cold has a rewarding quality. Similarly, humans made thirsty by exercise reduced cold water intake in comparison to warm water intake (Boulze et al 1983) but reported increased positive ratings for colder water (Boulze et al 1983;Sandick et al 1984).…”
Section: Introductionmentioning
confidence: 96%